THE ROLE OF COMMUNITY EDUCATION IN ENHANCING LITERACY CULTURE OF PRIMARY SCHOOL CHILDREN: A CASE STUDY AT THE COMMUNITY READING GARDEN IN LOMBOK TENGAH - Arif Widodo; Ashar Pajarungi Anar; Nursaptini; Deni Sutisna; Muhammad Erfan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Literacy is not only the responsibility of formal education institutions. One form of education in the community is a community library. This study aimed to describe the roles and challenges faced by community library forums in enhancing literacy culture. The subject of this study was a community reading garden as part of a community library forum. Data were collected in Kabupaten Lombok Tengah. This study applied a qualitative research design with a case study approach. Data collection was conducted through surveys, observation, and in-depth interviews, and the data were presented in the form of tables, diagrams, and descriptive narratives. The researchers extended observation time to ensure the validity of the findings. The main problems explored in this study included: What challenges do community library forums face? What is the role of the community library forum in enhancing the literacy culture of children in Lombok Tengah? The results revealed that the challenges faced by community library forums included issues of regeneration, inadequate facilities, limited book collections, low literacy culture, and non-optimal support from the government. The role of libraries in enhancing literacy culture included serving as facilitators, motivators, creators, and pioneers of the literacy movement in rural areas. The presence of the community library made children feel more enthusiastic about reading.